Strategic Management of Worker-Computer Interaction - Novikova, Irina V. (2020)
ABSTRACT Global threats, such as COVID-19, lead to the necessity to develop techniques that allow people who have to be isolated from each other to operate at full capacity, to produce goods, to provide services, to purchase goods and services, to study, to communicate, to have fun etc. Information and communication technology is a cornerstone for this. However, the effective usage of digital technologies depends on the competences of their users that is Worker- Computer interaction. Therefore, the article is devoted to the strategic management of the worker-computer interaction based on the digital potential of employment that is developed through the interaction of digital competence of an employee and digital components of a workplace. By conducting an extensive literature review about definitions and frameworks of digital competences presented by the European Parliament, the Organisation for Economic Co- operation and Development, the European Commission (DigComp), the National Research Council, the World Economic Forum, Japan Telework Association, the Skills for Employment Global Public-Private Knowledge Sharing Platform, the author broadens the scope of the concept of the digital potential of employment and gives the enhanced definitions of digital competence of an employee and digital components of a workplace. The author also scrutinizes the factors that influence the development of digital competences of an employee and digital components of a workplace, and suggests approaches to regulating and strategizing the digital potential of employment which can help to increase the effectiveness of the usage of digital technologies, labour productivity, human capital impact and to minimize the risks from the consequences of such a threat as coronavirus as well. Keywords strategic management, worker-computer interaction, the digital potential of employment, digital competence of an employee, digital (information) components of a workplace. ABOUT THE AUTHOR/S Irina V. Novikova novikovaiv5@gmail.com Doctor of Economics, Professor of the Economic and Financial Strategy Department at the Moscow School of Economics of Lomonosov Moscow State University, leading researcher of the Center for Strategic Studies at the Institute of Complex Systems Mathematical Research, Lomonosov Moscow State University New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).